Water Resource Management in Developing Countries: Synthesizing the Literature - Edy Sriyono (TEKNIK, 2022)
The literature on water management is extensive, yet most publications have been concerned with the context of the developed world and much less with the developing context. This study aims to examine the extant research, provide an overview of the empirical research in the field of water resource management in a developing context, and provide several future research suggestions. To perform this analysis, we use R and Scimeetr to compile the resources and visualize the result systematically. The raw data were then reviewed and analyzed further. We find evidence that the field of water resource management in a developing-world context is presently divided into five major themes: water resources, water quality, water management, sustainability, and climate change. We find evidence, too, that most literature in the field of water resource management in developing contexts ironically came from developed countries, such as the United States (265), the United Kingdom (128), and China (98). It is expected that this study could be used as a stepping stone to move the literature on water resource management, particularly in the developing world, forward.